Endogenous clues promoting remyelination in multiple sclerosis. Issue 3 (June 2022) - Lubetzki, Catherine; Zalc, Bernard; Kremer, David; Küry, Patrick
Abstract : Purpose of review: The introduction some 30 years ago of β-interferon, followed by a panel of immunomodulators and immunosuppressants has led to a remarkable improvement in the management of multiple sclerosis (MS) patients. Despite these noticeable progresses, which lower the number of relapses and thereby ameliorate patients' quality of life, preventing long-term progression of disability is still an unmet need, highlighting the necessity to develop therapeutic strategies aimed at repairing demyelinated lesions and protecting axons from degeneration. The capacity of human brain to self-regenerate demyelinated lesion has opened a field of research aimed at fostering this endogenous potential. Recent findings: The pioneer electron microscopic evidence by Périer and Grégoire [Périer O, Grégoire A. Electron microscopic features of multiple sclerosis lesions. Brain 1965; 88:937–952] suggesting the capacity of human brain to self-regenerate demyelinated lesion has opened a field of research aimed at fostering this endogenous potential. Here we review some recently identified mechanisms involved in the remyelination process, focusing on the role of electrical activity and the involvement of innate immune cells. We then provide an update on current strategies promoting endogenous myelin repair. Summary: Identification of therapeutic targets for remyelination has opened an active therapeutic field in MS. Although still in early phase trials, with heterogenous efficacy, the door for myelin regeneration in MS is now opened.